"Anoitecer": sculptural romanticism as a veil of ethnic-racial exclusion in public sculpture from Espírito Santo in the 1970s - Nunes, Fabíola Fraga; Miranda, Giuliano de; Cirillo, Aparecido José (Revista do Colóquio, 2022)
“Anoitecer” is the name of a sculpture that belongs to the collection of the National Museum of Fine Arts in Rio de Janeiro and is a wooden version of a monument to Dona Dominga from Espírito Santo. The bronze monument depicts the general form of an elderly, poor, black woman from the outskirts of the city, and its replica at the MNBA reveals exactly the woman at the end of her life, as suggested in the title given by the artist. The research aims to delve into the human aspect of public monuments, beyond the concrete nature of their construction. It will engage in a dialogue between the monument to Dominga by Carlo Crepaz and the issue of ethnic-racial prejudice. Based on Dominga, the study discusses the ongoing erasure of black and outskirts women in general.